RURAL EMPLOYMENT AND DECENT WORK IN ROMANIA - PATACHE, Laura; CHIRU, Claudiu; BEBEȘELEA, Mihaela (Annals of Spiru Haret University. Economic Series, 2018)
The aim of this paper is to study the Romanian rural employment and its perspective to achieve the decent work goals. The United Nation’s 2030 Agenda for Sustainable Development aims to ‘promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all’ (Goal 8 of 17, 2015). The decent work is a desideratum that reflects on the wellbeing of the population. The ILO’s Rural Employment and Decent Work Programme aims at minimizing rural decent work deficits that include higher rates of un- and under-employment (especially among youth and women); an alarming prevalence of child labour; a higher incidence of precarious work as wage work is mostly seasonal or casual; widespread informal activities; limited social protection; exposure to adverse working conditions due to poor labour standards coverage and monitoring; and little or no unionization or social dialogue